A STUDY ON THE PRAWN FISHERY OF NETRAVATI-GURUPUR ESTUARY, MANGALORE - Sukumaran, K K; Thippeswamy, O; Muniyappa, Y (Indian Journal of Fisheries, 2011)
Eight species of penaeids, one species of sergestid and three species ofcaridian were noticed in the Netravati-Gurupur estuary. The penaeids Penaeusindicus, P. monodon, Metapenaeus dobsoni, M. moyebi and M. monoceros werecommon. Peak recruitments of earty juveniles of P. indicus were in May, Juneand December and of M. dobsoni were in January and June-September